Dampak Pemberian Ekstrak “Simbagh Utak” (Hydnophytum formicarum) Terhadap Penurunan Kadar Asam Urat Darah pada Mencit (Mus musculus) Jantan Hiperurisemia - Gustria Ernis; Dewi Handayani; Agus Sundaryono (PendIPA Journal of Science Education, 2020)
One of Bengkulu's local culture is the utilization of medicinal plants by the people of Bengkulu, especially South Bengkulu, namely "Simbagh Utak" (Hydnophytum formicarum) for treating various diseases including Gout. However, they still use naturally, there is no scientific studied. This study was aimed to analyze the effect of “Simbagh Utak” (H. formicarum) on the reduction of serum uric acid levels in hyperuricemia male mice. This study used 25 male mice, that devided into 5 groups. The control group was given pellet feed (G1). We injected the high purine feed treatment per-oral to induce hyperuricemia (Negative control, G2) and then given H. formicarum extract 5.3mg/30gW (G3), 10.2mg/30gW (G4) and 21,2mg/30gW (G5). Uric acid measurements were performed using a digital method with easy touch /GCU. The tubers were extracted with maceration, eluent selection and isolation of the isolated components was carried out using thin layer chromatography and column chromatography. The extraction results were analyzed of functional groups using FTIR. The result showed that “simbagh utak” extract 5.3mg/30gW, 10.2mg/30gW and 21,2mg/30gW could reduced uric acid levels of hyperuricemia male mice 34.1%, 48.0% dan 53.4% respectively. On this basis, we conclude that "Simbagh Utak" extract could reduced levels of uric acid M. musculus males who have experienced a state of hyperuricemia (excess uric acid) very significantly at a dose of 21.2mg /30gW.